LncRNA THRIL Functions as a Marker for Carotid Artery Stenosis and Affects the Biological Function of Human Aortic Endothelial Cell - Wang F; Wang Y; Guo X (Dove Medical Press, 2023)
Fei Wang,1 Ying Wang,2 Xichun Guo3 1Department of Neurosurgery, Affiliated Hospital of Weifang Medical University, Weifang, People's Republic of China; 2Department of Medical Record Room, Affiliated Hospital of Weifang Medical University, Weifang, People's Republic of China; 3Department of Pharmacy, Affiliated Hospital of Weifang Medical University, Weifang, People's Republic of ChinaCorrespondence: Fei Wang, Department of Neurosurgery, Affiliated Hospital of Weifang Medical University, No. 2428 Yuhe Road, Kuiwen District, Weifang, Shandong, 261035, People's Republic of China, Tel/Fax +86-536-3081100, Email wangfeif2@163.comPurpose: Carotid artery restenosis (CAS) is a leading contributor to cerebrovascular diseases and one of the leading causes of death in the world. The purpose of this study was to assess the predictive efficiency of long non-coding RNA (lncRNA) TNFalpha-and hnRNP L-related immunoregulatory lncRNA (THRIL) and its association with the pathogenesis of CAS.Patients and Methods: The expression of THRIL was determined in patients with asymptomatic CAS and human aortic endothelial cell (HAEC) models induced by oxidized low-density lipoprotein (ox-LDL). The receiver operating characteristic (ROC) curve and Kaplan-Meier (K-M) drawings were constructed to predict the risk of poor prognosis in patients with CAS. The cell proliferation, death rate, and inflammation were detected by 3-(4,5-dimethyl-2-thiazyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT), flow cytometry, and enzyme-linked immunosorbent assay (ELISA) assays.Results: The relative expression of THRIL was elevated in patients with asymptomatic CAS. The findings of ROC curve indicated that THRIL had a predictive possibility on CAS. K-M finding and Cox regression analysis showed that the expression of THRIL and the degree of CAS were independent risk factors for poor prognosis in patients with CAS. THRIL was up-expressed in HAECs induced by ox-LDL. Down-regulation of THRIL could promote the proliferation of HAECs, inhibit cell apoptosis, and restrict cell inflammation.Conclusion: THRIL was a diagnostic and prognostic biomarker in CAS and played an important role in regulating the proliferation, apoptosis, and inflammation of HAECs induced by ox-LDL.Keywords: THRIL, carotid artery restenosis, prognosis, diagnosis, proliferation